Efficacy evaluation of neuromuscular blocking agents as adjuncts to intravenous regional anesthesia: a meta-analysis of randomized controlled trials - Yang, Yan; Sun, Shujun; Song, Guobin; Zhang, Jianfeng; Chen, Rui (Frontiers in Medicine, 2025)
PurposeTo evaluate the efficacy of neuromuscular blocking agents (NMBAs) as adjuncts to intravenous regional anesthesia (IVRA).MethodsTwo researchers independently searched PUBMED, EMBASE, the Cochrane Library databases, and CBM for randomized controlled trials assessing the efficacy of NMBAs as adjuvants in IVRA.ResultsThis meta-analysis included 420 patients from 7 randomized controlled trials. Compared to IVRA using local anesthetics alone, the adjunctive use of NMBAs significantly shortened the onset time of sensory block [mean difference (MD) = −1.38 min, 95% CI: −2.02 to −0.75; P < 0.01] and motor block (MD = −2.39 min, 95% CI: −4.67 to −0.12; P = 0.04). Moreover, NMBAs prolonged the duration of motor block (MD = 6.97 min, 95% CI: 0.06 to 13.88; P = 0.05). However, no significant improvement was observed in the duration of pain relief (MD = 4.24 min, 95% CI: −1.43 to 9.91; P = 0.14).ConclusionAs adjuncts to IVRA, NMBAs significantly reduce the onset time of sensory and motor blocks compared to local anesthetics alone. Additionally, NMBAs prolong the duration of motor block. These agents enhance the efficacy of IVRA by optimizing neuromuscular blockade while maintaining anesthetic quality comparable to standard IVRA techniques.